2020
DOI: 10.1002/met.1886
|View full text |Cite
|
Sign up to set email alerts
|

Projected increase of the East Asian summer monsoon (Meiyu) in Taiwan by climate models with variable performance

Abstract: The active phase of the East Asian summer monsoon (EASM) in Taiwan during May and June, known as Meiyu, produces substantial precipitation for water uses in all sectors of society. Following a companion study that analysed the historical increase in the Meiyu precipitation, the present study conducted model evaluation and diagnosis based on the EASM lifecycle over Taiwan. Higher and lower skill groups were identified from 17 Couple Model Intercomparison Project Phase 5 (CMIP5) models, with five models in each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…From the figure, it is obvious that SW winds dominate in September 2010 and the average wind speed is about 3~7 m/s. This is consistent with the previous study [31] that showed SW winds dominating from July to September in Taiwan. In addition to wind data on a specific location, the wind field in the computational domain at 01:00 UTC on 9 September 2010 is obtained from the observation of the satellite scatterometer ASCAT [58].…”
Section: Cold Eddy and Wind Effectsupporting
confidence: 94%
See 2 more Smart Citations
“…From the figure, it is obvious that SW winds dominate in September 2010 and the average wind speed is about 3~7 m/s. This is consistent with the previous study [31] that showed SW winds dominating from July to September in Taiwan. In addition to wind data on a specific location, the wind field in the computational domain at 01:00 UTC on 9 September 2010 is obtained from the observation of the satellite scatterometer ASCAT [58].…”
Section: Cold Eddy and Wind Effectsupporting
confidence: 94%
“…From the figure, it is obvious that SW winds dominate in September 2010 and the average wind speed is about 3~7 m/s. This is consistent with the previous study [31] that showed SW winds dominating from July to September in Taiwan. [58].…”
Section: Input Wind Datasupporting
confidence: 94%
See 1 more Smart Citation
“…Numerous GCMs have been found to possess insufficient features to simulate regional climate characteristics [64]. For example, mountains are a problem that has not been solved in all models [65] such that some studies have not considered the effects of local terrains [66] on water yield. These insufficiencies increase the number of discrepancies between simulation and observation results.…”
Section: Suitability Of Various Circulation Models For Small Areasmentioning
confidence: 99%
“…Focusing on Taiwan, evidence of altering rainfall regime induced by climate change was indicated by several recent studies [32][33][34][35][36][37][38]. However, little research has examined the changes in streamflow regime in Taiwan, with the exception of Yeh et al [39] who investigated the long-term streamflow trend in northern Taiwan using the Mann-Kendall test.…”
Section: Introductionmentioning
confidence: 99%